Value of probe-based confocal laser endomicroscopy (pCLE) and dual focus narrow-band imaging (dNBI) in diagnosing early squamous cell neoplasms in esophageal Lugol’s voiding lesions - Prueksapanich, Piyapan; Pittayanon, Rapat; Rerknimitr, Rungsun; Wisedopas, Naruemon; Kullavanijaya, Pinit (Endoscopy International Open, 2015)
Background and study aims: Lugol’s chromoendoscopy provides excellent sensitivity for the detection of early esophageal squamous cell neoplasms (ESCN), but its specificity is suboptimal. An endoscopy technique for real-time histology is required to decrease the number of unnecessary biopsies. This study aimed to compare the ESCN diagnostic capability of probed-based confocal laser endomicroscopy (pCLE) and dual focus narrow-band imaging (dNBI) in Lugol’s voiding lesions.Patients and methods: Patients with a history of head and neck cancer without dysphagia were recruited. Lugol’s voiding lesions larger than 5 mm were sequentially characterized by dNBI and pCLE by two independent operators. Finally, all lesions larger than 5 mm were biopsied followed by histological analysis, which is considered to be the gold standard in cancer diagnosis. The primary outcomes were the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and the accuracy of the two techniques.Results: In total, 44 patients were enrolled with a mean age of 60 years; 80 % were male. Twenty-one Lugol’s voiding lesions larger than 5 mm were detected in 12 patients. Seven lesions (33 %) from four patients were histologically diagnosed as ESCNs (four with high grade dysplasia and three with low grade dysplasia). The other 14 lesions were histologically confirmed as non-neoplastic: active esophagitis, glycogenation with inflammation, acute ulcer, inlet patch, and unremarkable changes. The sensitivity, specificity, PPV, NPV, and accuracy of pCLE vs. dNBI were 83 % vs. 85 %, 92 % vs. 62 %, 83 % vs. 54 %, 92 % vs. 89 %, and 89 % vs. 70 %, respectively (NS).Conclusions: Asymptomatic patients with a history of head and neck cancer underwent Lugol’s chromoendoscopy based ESCN surveillance. Further characterization of the Lugol’s voiding lesions by advanced imaging showed that both pCLE and dNBI provided good sensitivity in diagnosing ESCN, and pCLE tended to provide higher specificity, PPV, and accuracy than dNBI. Perhaps the trend of lower specificity of dNBI in this study was possibly because of the interference from Lugol’s stain on the interpretation of intrapapillary capillary loops (IPCLs). Further study is required to seek a significant difference in the performance of dNBI and pCLE in a larger group of patients.